جودة أنشطة التدقيق الداخلي بالمؤسسات الاقتصادية الجزائرية - دراسة ميدانية من وجهة نظر المدققين الداخليين بشركات المساهمة بولاية عنابة - كبلوتي, حمزة; شيخي, بلال (جامعة الوادي - University of Eloued, 2022)
The objective of this study is to try to detect the quality of internal audit activities in Algerian economic companies. To achieve this objective, a study tool (questionnaire) was developed, consisting of 74 items. Where the questionnaire was distributed to the sample representing the study population, which are the internal auditors in the 76 joint stock companies in the wilaya of Annaba. To analyse the questionnaire and test the hypotheses, statistical software (SPSS) was used. The results showed that internal audit activities in companies are of good quality and are measured in terms of (independence of the internal auditor, admissibility and effectiveness of the internal auditor, quality of the internal auditor's performance, good interaction of the internal audit with the rest of the governance mechanisms)
The quality of internal audit activities in Algerian economic companies An empirical study of the point of view of the internal auditors in the joint- stock companies in the wilaya of Annaba
مقال
Keywords: عمل المدقق الداخلي ; استقلالية المدقق الداخلي ; أهلية المدقق الداخلي ; جودة التدقيق الداخلي; internal auditor performance quality ; internal auditor independence ; internal auditor admissibility ; internal audit quality